Natural killer cells in non-hematopoietic malignancies - Desbois, Mélanie; Rusakiewicz, Sylvie; Locher, Clara; Zitvogel, laurence; Chaput, Nathalie (Frontiers in Immunology, 2012)
Natural killer (NK) cells belong to the innate immune system and were initially described functionallywise by their spontaneous cytotoxic potential against transformed or virus-infected cells. A delicate balance between activating and inhibiting receptors regulates NK cell tolerance. A better understanding of tissue resident NK cells, of NK cell maturation stages and migration patterns has evolved allowing a thoughtful evaluation of their modus operandi. While evidence has been brought up for their relevance as gate keepers in some hematopoietic malignancies, the role of NK cells against progression and dissemination of solid tumors remains questionable. Hence, many studies pointed out the functional defects of the rare NK cell infiltrates found in tumor beds and the lack of efficacy of adoptively transferred NK cells in patients. However, several preclinical evidence suggest their anti-metastatic role in a variety of mouse tumor models.. In the present review, we discuss NK cell functions according to their maturation stage and environmental milieu, the receptor/ligand interactions dictating tumor cell recognition and recapitulate translational studies aimed at deciphering their prognostic or predictive role against human solid malignancies.